Young Malaysians' travel lifestyles and intentions: The moderating effects of personal characteristics and perceived risks - Cheah, Swee Ting; Lim, Khong Chiu; Kayat, Kalsom (2012)
The young travellers' segment is an emerging market for the travel and hospitality industry.However, the negligence in this lucrative market segment has caused failure in collecting statistics as well as having specific marketing plans and policies by most countries including Malaysia.In addition, there is very little study conducted regarding travelling activities among young Malaysians.This paper focuses on the travel lifestyles and intentions of young Malaysians in travelling overseas.Personal characteristics and perceived risks are examined to study their moderating effects on the relationship between travel lifestyles and intentions.Thus, this study targets to remedy the shortcomings of prior research pertaining to young Malaysians' outbound tourism patterns.